The role of large traders in driving sustainable agricultural intensification in smallholder farms: Evidence from Kenya - Mulwa, C.K.; Muyanga, M.; Visser, M. (Wiley, 2021)
Pervasive threats of climate change and land degradation have compounded the inherent low farm productivity problem in sub-Saharan Africa. Though sustainable agricultural intensification practices have been shown to improve the resilience of farm production in the face of these emerging threats, they suffer low adoption rates typical of any technology adoption in these regions. Recent evidence points to an emergence of large traders in smallholder grain markets of countries in sub-Saharan Africa. Given their big financial and operational capacities, the hypothesis is that they can drive the elusive transformation in agri-food systems by enhancing sustainable production and marketing for smallholder farmers. This study tests this hypothesis using a decade-long large-panel dataset from Kenya. A dynamic random effects Probit model and a control function approach are used to evaluate the dynamism in adopting sustainable agricultural inputs and the effect of large grain traders in enhancing the adoption of these inputs at the farm level. Results indicate that sales to large grain traders lead to higher adoption of inorganic fertilizer and improved seed, key agricultural intensification inputs. Land ownership is also shown to be a key success factor for entry into large-grain-trader markets. Lastly, the adoption of improved seed and organic manure is persistent across time, indicating state dependence in using these inputs. These results suggest that strategies to foster engagements between large grain traders and farmers can enhance the uptake of sustainable intensification inputs. Such strategies should be accompanied by efforts to improve access to these markets by resource-poor farmers who are primarily smallholders.